Optimalisasi dan Strategi Penjualan Baju Thrifting Melalui Implementasi E-commerce CMS PrestaShop di Jalan Sigambal Rantauprapat - Ardiansyah, Sandi; Harahap, Syaiful Zuhri; Munthe, Ibnu Rasyid (Universitas Labuhanbatu, 2024)
Abstract This study aims to explore effective digital marketing strategies for enhancing thrift clothing sales in the era of information technology. With the rapid development of technology and increasing market competition, businesses that previously relied solely on social media platforms like Instagram now need to adapt by utilizing more professional e-commerce platforms. This research compares specific thrift platforms with websites using CMS Prestashop in attracting consumer attention. The methods employed include observation, interviews, and literature reviews, aiming to understand the interaction patterns between sellers and buyers, as well as the operational dynamics within thrift businesses. The findings are expected to provide valuable insights for entrepreneurs in formulating more effective digital marketing strategies, thereby increasing competitiveness and sustainability in an increasingly competitive market.